Cultivation of Religious Moderation Values through Ngidang Tradition in Kelurahan 1 Ulu Palembang - Achmad Fadil; Ani Marlia; Muhammad Ghazali; Dwi Setiawati; Agustri Regita Cahyani; Syarnubi, Syarnubi; Muhamad Fauzi; Septia Fahiroh (Tadrib: Jurnal Pendidikan Agama Islam, 2025)
This research discusses the "Cultivation of Religious Moderation Values through the Ngidang Tradition in Kelurahan 1 Ulu Palembang." Amid growing religious exclusivism and cultural erosion, this study addresses the lack of scholarly attention on how local traditions can serve as a medium for promoting religious moderation. The Ngidang tradition is explored as a cultural approach to instill religious moderation through local arts in Palembang, specifically in 1 Ulu Village. The research focuses on how Majelis Ta’lim An Nur utilizes this tradition to cultivate values such as I'tidal (fairness), Tasamuh (tolerance), Asy-Syura (deliberation), I'tiraf al-'Urf (cultural appreciation), and Al-Qudwah (leadership). Employing a qualitative method, data were collected through observation, interviews, and documentation, then analyzed using Miles and Huberman's interactive model. The findings reveal that the Ngidang tradition remains preserved and actively practiced by the local community, supported by economic motives and government initiatives. However, challenges persist, including social prestige, limited cultural awareness, and economic constraints. This research makes a theoretical contribution to the discourse on integrating indigenous culture in fostering religious moderation, emphasizing its relevance in contemporary pluralistic societies.